Outcome after Turndown for Elective Abdominal Aortic Aneurysm Surgery. (November 2017) - Whittaker, Joshua D.; Meecham, Lewis; Summerour, Virginia; Khalil, Sheirin; Layton, Georgia; Yousif, Marianne; Jennings, Adrian; Wall, Micheal; Newman, Jeremy
Abstract : Objectives: The aim was to assess the survival of patients who had been turned down for repair of an abdominal aortic aneurysm (AAA) and to examine the factors influencing this. Methods: This was a retrospective observational study of a prospectively maintained database of all patients turned down for AAA intervention by the Black Country Vascular Network multidisciplinary team (MDT) from January 2013 to December 2015. Data on AAA size, cardiopulmonary exercise testing (CPET) and cause of death were recorded. Results: There were 112 patients. The median age at turndown was 83.9 years (IQR 10.2 years). The median AAA size at turndown was 63 mm (IQR 16.7 mm). The median follow-up time after turndown was 324 days (IQR 537.5 days). Sixty-four patients (57.1%) were deceased after 2 years, with a median survival time of 462 days (IQR 579 days). Patients who died had a significantly larger AAA dimension (median 65 mm, IQR 18.5 mm) than those surviving to date (median 59 mm, IQR 10 mm, p = .004). Using Cox regression analysis, the probability of 1 year survival in the whole population was 0.614. The probability of 2 year survival was 0.388. When accounting for age, gender, AAA dimension, and British Aneurysm Repair risk score, no factors had significant influence over survival. Of the 64 deceased patients, 30 had an accessible cause of death: 36.7% of these were due to ruptured AAAs. There was no significant difference in AAA size between those dying of ruptures and those dying of other causes ( p = .225, mean 74 mm and 67 mm respectively). Conclusions: Being turned down for AAA repair carries a significant short-term risk of mortality. Those turned down for repair carried significant levels of comorbid disease but no factors considered were found to be independently predictive of the length of survival.